Characterization of loss and bandwidth performance of reflectarray antenna based on lumped components - Ismail, Muhammad Yusof (2010)
Lumped components are used to represent the reflectarrays designed using different commercially available materials. The loss performance and the effect of material properties on the reflectarray antennas are discussed in terms of the lumped components which are used in the equivalent circuit analysis. The bandwidth performance of reflectarrays designed with different materials is discussed using reflection loss and reflection phase plots obtained by equivalent circuit analysis. Furthermore the results obtained by equivalent circuit modeling are compared with the results obtained using CST Microwave Studio simulations and a close agreement between all the results has been demonstrated. The dielectric permittivity (εr) of materials investigated in this work ranges between 2.08 to 13 and the loss tangent (tanδ) values vary from 0.0003 to 0.025 while the reflection loss values obtained by equivalent circuit analysis varied from 0.179 dB to 6.875 dB and a variation in 10% and 20 % bandwidth is observed from 84 MHz to 360 MHZ and 126 MHZ to 540 MHz respectively based on the respective material properties.